Analysis of different methods to estimate fecundity in bivalve molluscs. Issue 1 (2nd January 2016) - Cáceres-Puig, Jorge I.; Saucedo, Pedro E.; Chávez-Villalba, Jorge; Cáceres-Martínez, Carlos
Abstract: We analyzed the advantages and disadvantages of three methods to estimate potential fecundity in the bivalve molluscs Pinctada mazatlanica and Atrina maura, both species having commercial value in northwestern Mexico. Data of gonad samples collected during the breeding season in March 1999 ( P. mazatlanica ) and March 2003 ( A. maura ) were processed with histological techniques combined with Cavalieri's Principle; stereological analysis of the gonad with the caliper method; and estimation of the theoretical radius of oocytes. These estimates were compared to a reference value obtained from direct counts of the number of oocytes stripped from the gonad. Compared to other methods, potential fecundity determined with the caliper method was more accurate in both species: A. maura (9.8–15 × 10 6 cells ind −1 and P. mazatlanica (10.8–17 × 10 6 cells ind −1 ). The potential of the caliper method, combined with image analysis software may offer accurate estimates of aspects of reproduction in different bivalve species, which has direct applications in hatcheries and conservation programs.